2018
DOI: 10.17358/ijbe.4.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Consumer’s Attitude and Willingness to Pay for Organic Rice

Abstract: Government's support for Go Organic program provides a significant effect on the increasing organic land from only 71 thousand hectares in 2010 to 113 thousand hectares in 2014. This is caused by the shifting lifestyle of consumers who are more concerned about health. Rice as one of carbohydrate sources consumed by Indonesian people has an organic variant which is favored by many consumers. This study involved 100 households which were intentionally selected based on their convenience and readiness to be inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
1
6
0
6
Order By: Relevance
“…Integrated Marketing consists of product components, channels and communication to create value for consumers, one of which is consumer trust. Consumer trust on the quality of a product is an attitude that will be manifested in their consumption behavior (Nur et al 2018). Linking the dimension of consumer trust with Integrated Marketing component, in this study, only studied three dimensions of consumer trust: transparency (degree of information disclosure from company to consumer), incentive (alignment on the trust of company employees as well as fulfillment of consumer needs) and partnership helping consumers or responding to consumer complaints).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated Marketing consists of product components, channels and communication to create value for consumers, one of which is consumer trust. Consumer trust on the quality of a product is an attitude that will be manifested in their consumption behavior (Nur et al 2018). Linking the dimension of consumer trust with Integrated Marketing component, in this study, only studied three dimensions of consumer trust: transparency (degree of information disclosure from company to consumer), incentive (alignment on the trust of company employees as well as fulfillment of consumer needs) and partnership helping consumers or responding to consumer complaints).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of willingness to pay (WTP) for organic rice, Steinhübel et al (2018) reported that, based on a study in the city of Jogjakarta, people were willing to pay an average premium price of 20% more for certified organic rice compared to the price they usually pay for conventional rice. A Similar study by Fathia et al (2018) conducted in the city of Bogor showed that WTP (in consumers' average value) on organic rice was IDR 20,000 per kilogram. This value was IDR 4,000 (or 20%) higher than the lowest price for organic rice sold in markets.…”
Section: Green Revolution's Role and Impact: Organic Farming Potentiamentioning
confidence: 80%
“…Nilai kesediaan membayar (willingness to pay) beras organik di setiap daerah tentu berbeda karena perbedaan nilai daya beli yang dipengaruhi tingkat pendapatan, perbedaan karakteristik konsumen, dan jenis beras organik yang dijual. Riana et al (2019) (Fathia, 2018), sedangkan nilai rata-rata maksimum beras organik di Pontianak sebesar Rp 26.120 per kilogram (Setiyadi et al, 2016). Nilai rataan willingness to pay beras pandan wangi organik di Bandung sebesar Rp 24.000 per kilogram (Yuningsih, 2016).…”
Section: Pendahuluanunclassified